Amino acid profile in overweight and obese prepubertal children – can simple biochemical tests help in the early prevention of associated comorbidities? - Bugajska, Jolanta; Berska, Joanna; Wójcik, Małgorzata; Sztefko, Krystyna (Frontiers in Endocrinology, 2023)
Background It is accepted that plasma branched-chain amino acids (BCAAs) and aromatic amino acids (AAAs) are closely related to metabolic risk. Arterial hypertension, metabolic syndrome, endothelial dysfunction, inflammation, and metabolic dysfunction-associated fatty liver disease (MAFLD) are frequently seen in obese patients. Many attempts have been made to find biochemical indicators for the early detection of metabolic complications in children. It is not known if different amino acid profiles and BCAA and AA concentrations in overweight and obese children correlate with chemerin, proinflammatory, and simple biochemical markers. Thus, the study aimed to find out the early markers of cardiovascular disease and MAFLD in overweight and obese children. Materials and methods The study included 20 overweight and obese children (M/F 12/8; mean age 7.7 ± 2.3 years; BMI 26.8 ± 5.0 kg/m2) and 12 non-obese children (control group) (M/F 4/8; mean age 6.5 ± 2.2 years; BMI 14.8 ± 1.5 kg/m2). The following plasma amino acids were measured: aspartic acid, glutamic acid, serine, asparagine, glycine, glutamine, taurine, histidine, citrulline, threonine, alanine, arginine, proline, tyrosine, methionine, valine, isoleucine, leucine, phenylalanine, tryptophan, ornithine, and lysine. Chemerin, high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), and basic biochemistry parameters were measured. Results The mean plasma levels of leucine, isoleucine, valine, phenylalanine, tyrosine, glutamic acid, and alanine were significantly higher in overweight and obese children than in the control group (p<0.03–p<0.0004). Conversely, the mean values of serine, asparagine, glutamine, and citrulline were significantly lower in overweight and obese children than in the control group (p<0.03–p<0.0007). Isoleucine, leucine, valine (BCAAs) tyrosine, and phenylalanine (AAAs) levels showed a positive correlation with uric acid, ALT, hs-CRP, and chemerin (r=0.80–0.36; p<0.05-p<0.00001), but not with IL-6. The mean values of glucose, IL-6, hs-CRP, chemerin, uric acid, and ALT were significantly higher in overweight and obese children than in the control group (p<0.03–p<0.00002). In contrast, the lipid profile did not differ between groups. Conclusion An abnormal amino acid profile in overweight and obese pre-pubertal children, accompanied by elevated ALT and UA observed in the studied cohort, may suggest early metabolic disturbances that can potentially lead to metabolic syndrome, or MAFLD, and increased cardiovascular risk.